2008
DOI: 10.4269/ajtmh.2008.78.1012
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Hepatitis E Virus (HEV) in Swine Workers

Abstract: The aim of this work was to study the prevalence of hepatitis E virus (HEV) and the risk factors for the acquisition of the virus in a population in contact with swine and unexposed to swine. A total of 198 individuals, 97 unexposed (49%) and 101 exposed (51%) to swine, were tested for the presence of HEV infection. The prevalence of anti-HEV IgG in the exposed group was 18.8% versus 4.1% in the unexposed to swine group. People exposed to swine were observed to be 5.4 times (P = 0.03) at risk of having anti-HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 26 publications
9
66
0
4
Order By: Relevance
“…6, P=0 . 01) for anti-HEV IgG seroprevalence confirmed by immunoblot [94]. Conversely, the EL3 case-control study found that drinking well water and contact with surface was not related to HEV infection [52].…”
Section: Potential For Water-borne Transmissionmentioning
confidence: 95%
“…6, P=0 . 01) for anti-HEV IgG seroprevalence confirmed by immunoblot [94]. Conversely, the EL3 case-control study found that drinking well water and contact with surface was not related to HEV infection [52].…”
Section: Potential For Water-borne Transmissionmentioning
confidence: 95%
“…45,46 In Madagascar, we found that HEV seroprevalence among slaughterhouse workers reached 33.3% in the district of Fianarantsoa, but the average seropositivity (14.1%) could be considered as modest when compared with other studies. Indeed, studies in Spain, 47 Germany, 48 Switzerland, 49 and in the United States 24,50 have shown that HEV seroprevalence in exposed human populations, such as veterinarians and slaughterhouse workers, can reach more than 35%, whereas in non-exposed humans (i.e., blood donors) the seroprevalence is significantly lower. Further studies are needed to measure the seroprevalence of HEV in the Malagasy general population, and to determine if pig breeders are at higher risk of contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposures to farm animals, especially swine, have been associated with HEV infection in some studies in Africa, Europe, and the United States (73,133,145,146), but a recent study in Thailand found no difference between the seroprevalence among swine workers and that among others in the local population (147). Inadequately treated manure from swine farms represents another potential source of environmental contamination (148)(149)(150).…”
Section: Epidemiologic Patterns Of Hepatitis E Virus Infectionmentioning
confidence: 99%